Effect of acid leaching conditions on impurity removal from silicon doped by magnesium - Stine Espelien; Jafar Safarian (AIMS Energy, 2017)
The effect of magnesium addition into a commercial silicon and its leaching refining behavior is studied for producing solar grade silicon feedstock. Two different levels of Mg is added into a commercial silicon and the leaching of the produced alloys by 10% HCl solution at 60 ℃ for different durations is performed. It is shown that the microstructure of the alloy and in particular the distribution of eutectic phases is dependent on the amount of the added Mg. Moreover, the metallic impurities in silicon such as Fe, Al, Ca and Ti are mainly forming silicide particles with different compositions. These silicides are physically more detached from the primary silicon grains and their removal through chemical and physical separation in leaching is better for higher Mg additions. It is observed that the leaching is more effective for the purification of smaller silicon particles produced from each Mg-doped silicon alloy. It is shown that acid leaching by the applied method is effective to reach more than 70% of phosphorous removal. It is also shown that the purity of silicon is dependent on the total Mg removal and effectiveness of leaching on removing the Mg2Si phase.